Acute Effect of Repeated Sprint and Aerobic Endurance Training on Foxp3+ Regulatory T Cells and Cytokine Levels - (:unkn) unknown (TURKISH SOC IMMUNOLOGY, 2021)
Objective: The aim of our study was to investigate the acute effect of repeated sprints and aerobic endurance training on Foxp3+ T regulatory cells and cytokines. Materials and Methods: The study population consisted of 16 sprinters and 16 long distance runners. Each subject was divided into his/her own branch as sprinting and distance training. Within the scope of the study, the height, body weight, sporting age, Foxp3+ T regulatory cells and cytokine values of subjects were recorded. Immunity subparameters were compared in venous blood samples taken before and after training. The Wilcoxon test was used to compare the values before and after training with level of statistical significance accepted as p<0.05. Results: A statistically significant change was not observed for Foxp3+ T regulatory cells before and after training in sprinter (p=0.47) and distance runners (p=0.52). Sprinters had increased IL-2 (p=0.00), IL-4 (p=0.00), IL-10 (p=0.02), IL-17 (p=0.000) and TNF-alpha (p=0.000), decreased IL-6 (p=0.000) and unchanged IFN-gamma levels (p=0.81). Distance runners had increased IL-4 (p=0.000), IL-10 (p=0.000), IL-17 levels (p<0.00), decreased TNF-alpha (p=0.00), IL-2 (p=0.05) and unchanged IFN-gamma (p=0.15) and IL-6 (p=0.15). Conclusion: Immune system is affected by the intensity and type of exercise. It can be said that anaerobic exercises like sprinting with high intensity supress the immune system more severely.
Keywords: Immune response to exercise; cytokines; Foxp3+ T regulatory cells